2016
DOI: 10.1111/bju.13593
|View full text |Cite
|
Sign up to set email alerts
|

ProCare Trial: a phase II randomized controlled trial of shared care for follow‐up of men with prostate cancer

Abstract: Well-structured shared care for men with low- to moderate-risk prostate cancer is feasible and appears to produce clinically similar outcomes to those of standard care, at a lower cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
85
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 36 publications
1
85
0
Order By: Relevance
“…Among those six papers that detected the quality of life, five papers detected the differences between the two arms at the end of the intervention, and one paper compared the outcomes between the beginning and the end of the shared care, but none of these papers detected any significant difference [313334353637]. As for the survivors’ psychological status, the two papers evaluated the survivors’ psychological distress level, finding no significant difference between the intervention group and control group [3137]. Besides, the paper that assessed the survivorship worries found no difference before and after the shared care, but there was a borderline difference between the two groups after the shared care [38].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among those six papers that detected the quality of life, five papers detected the differences between the two arms at the end of the intervention, and one paper compared the outcomes between the beginning and the end of the shared care, but none of these papers detected any significant difference [313334353637]. As for the survivors’ psychological status, the two papers evaluated the survivors’ psychological distress level, finding no significant difference between the intervention group and control group [3137]. Besides, the paper that assessed the survivorship worries found no difference before and after the shared care, but there was a borderline difference between the two groups after the shared care [38].…”
Section: Resultsmentioning
confidence: 99%
“…The results include the satisfaction with the follow-up [343738], the satisfaction towards the PCPs [36], the attitudes toward the cooperation between health providers [33], the attitudes toward the information they received [39], survivorship unmet needs [37], and the preference for the care provider [3738]. From the survivor report results, the cooperation between health care practitioners improved (p = 0.025 and p = 0.004 in two out of four items) in the intermediate outcomes [33], and Emery et al found the survivors in the shared care group would prefer shared care in the follow-up after the study (p = 0.07) [37]. Apart from these, the studies found no other significant differences between the two arms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…18 19 The results of an Australian randomised control trial examining integrated care with hospitals and general practitioners (GPs) for patients with prostate cancer also demonstrated that this was a safe and acceptable model of care at lower cost to the healthcare system. 20 GPs feel confident and enabled to contribute to long-term cancer care 21 and cancer survivors are satisfied with care delivery in primary care. 22 There have been a number of studies examining follow-up of lung cancer in different settings.…”
Section: Introductionmentioning
confidence: 99%